First record of Nesomesochorinae (Hymenoptera: Ichneumonidae) from America north of Mexico with descriptions of two new species of Nonnus Cresson - Wahl, David B.; Bennett, Andrew M.r. (Zootaxa, 2020)
The subfamily Nesomesochorinae is recorded for the first time from America north of Mexico. Two new species of Nonnus (Hymenoptera: Ichneumonidae: Nesomesochorinae) are described, both from Arizona, USA and Mexico. Diagnostic characters and figures are provided to distinguish these two new species from congeners in North and Central America.